An Unusual Case of an Intraperitoneal Foreign Body - Khalid, Shazra; Malik, Arslan Sharif; Tahir Kheli, Muhammad Uzair ilyas; Hussain, Aamir; Afzal, Hasnain; Baksh, Sadia Allah (Pakistan Armed Forces Medical Journal, 2025)
We report a case of an intraperitoneal foreign body lodged in the rectum by the patient. Our patient was a 42-year-old male, who presented within 48 hours of inserting the event. Radiologically, pneumoperitoneum was present but intraoperatively, no gut perforation was found. This study aims to report managing such a case while emphasizing the possibility of concealed gut perforation. We want to emphasize the importance of a surgeon demonstrating compassion while collecting claims of such nature, owing to the numerous associated social taboos. It is observed that patients insert objects through the rectum for sexual gratification, however, during history taking they tend to deny it. This case highlights the delayed nature of presentation in a case that needed a crucial multidisciplinary approach for management